(untitled) (Colombia Medica, 2016)
We read with high interest the article by Alzate et al1, and hereby we share comments about its design, study population and statistical approach along with revisiting some key concepts of the disease. The prevalence of preeclampsia in Colombia is 4.5%2 and a case-control study is appropriate to investigate risk and protective factors associated in such setting and their corresponding Odds Ratios. However, in the population studied by Alzate et al, the proportion of preeclampsia is 10% (387/3866 ). Under this scenario, a retrospective cohort study design is also appropriate and allows for direct estimation of incidences and relative risks could also be considered with direct estimates of relative risk. The exposure under study here (calcium prescription) is easy to measure from medical or administrative records or electronic files, therefore its comprehensive assessment in the whole population is feasible, cheap and easy to detect. Case-control studies are usually recommended when these requirements are not met for the exposure variable.